The Influence of Personal Selling, Innovation Capacity, and Distribution Effectiveness on the Marketing Performance of MSMEs with a Competitive Environment as a Moderation Variable - Nanik Wahyuningtiyas; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardana (Jurnal Bintang Manajemen, 2024)
This study aims to analyze the influence of personal selling, innovation capacity, and distribution effectiveness on the marketing performance of MSMEs, as well as the role of moderating the competitive environment. This study uses the Structural Equation Modeling (SEM) approach with 387 MSME respondents in Indonesia. The results showed that personal selling and innovation capacity had a positive and significant influence on marketing performance, while distribution effectiveness did not show a significant influence. The competitive environment plays a significant moderating variable on the influence of innovation capacity but does not moderate the relationship between personal selling and distribution and marketing performance. These findings indicate that to improve marketing performance, MSMEs need to focus on personal selling strategies and product innovation, especially in markets with a high level of competition. This research also provides recommendations for MSMEs to improve their distribution strategies and better adapt to the development of marketing technology.